Stability of psilocybin and its four analogs in the biomass of the psychotropic mushroom Psilocybe cubensis - Gotvaldová, Klára; Hájková, Kateřina; Borovička, Jan; Jurok, Radek; Cihlářová, Petra; Kuchař, Martin (Drug testing and analysis, 2021)
Psilocybin, psilocin, baeocystin, norbaeocystin, and aeruginascin are tryptamines structurally similar to the neurotransmitter serotonin. Psilocybin and its pharmacologically active metabolite psilocin in particular are known for their psychoactive effects. These substances typically occur in most species of the genus Psilocybe (Fungi, Strophariaceae). Even the sclerotia of some of these fungi known as "magic truffles" are of growing interest in microdosing due to them improving cognitive function studies. In addition to microdosing studies, psilocybin has also been applied in clinical studies, but only its pure form has been administrated so far. Moreover, the determination of tryptamine alkaloids is used in forensic analysis. In this study, freshly cultivated fruit bodies of Psilocybe cubensis were used for monitoring stability (including storage and processing conditions of fruiting bodies). Furthermore, mycelium and the individual parts of the fruiting bodies (caps, stipes, and basidiospores) were also examined. The concentration of tryptamines in final extracts was analyzed using ultra-high-performance liquid chromatography coupled with mass spectrometry. No tryptamines were detected in the basidiospores, and only psilocin was present at 0.47 wt.% in the mycelium. The stipes contained approximately half the amount of tryptamine alkaloids (0.52 wt.%) than the caps (1.03 wt.%); however, these results were not statistically significant, as the concentration of tryptamines in individual fruiting bodies is highly variable. The storage conditions showed that the highest degradation of tryptamines was seen in fresh mushrooms stored at -80°C, and the lowest decay was seen in dried biomass stored in the dark at room temperature.
Keywords: Psychotropic Drugs; Chromatography, High Pressure Liquid; psychotropní léky; tandemová hmotnostní spektrometrie; stability; Psilocybe; Biomass; Tandem Mass Spectrometry; psilocybin; mushrooms; LC-MS; vysokoúčinná kapalinová chromatografie; Psilocybin; tryptamines; biomasa